PENGARUH EXPERIENTIAL MARKETING FITUR DAN TRUST TERHADAP KEPUASAN PENGGUNA APLIKASI SHOPEE (Studi pada Mahasiswa Fakultas Ekonomi Universitas Abdurachman Saleh Situbondo) - Yudha Praja (Growth, 2020)
This study examines the effect of experiential marketing, features and trust on the satisfaction of Shopee application users, namely the students of the Faculty of Economics, Abdurachman Saleh University, Situbondo. The data analysis methods used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, f test, dominant test, and coefficient of determination. Multiple linear regression results show that experiential marketing, features and trust variables have a positive influence on the Shopee application user satisfaction variable, it is shown in the results of multiple linear regression analysis, namely Y = 3.348E-17 + 0.250 + 0.270 + 0.194 + e. It shows that the tcount value of the experiential marketing variable is 2.408 > 1.983 ttable. The feature variable is t. 4.078 > 1.983. The trust variable is t. 3.280 > t. Saleh Situbondo as a Shopee application user. Fcount 44,364 > Ftable 2,81, so it can be concluded that experiential marketing, features and trust variables have a simultaneous effect on Shopee application user satisfaction. Based on the dominant test the value of the service feature variable is greater than the other variables of 4.078.